Problems Identification and Efforts of Inclusive Elementary Schools in Service Improvement: An Integrative Literature Review - Muntamah, Bening Siti; Nawangsari, Nur Ainy Fardana; Yoenanto, Nono Hery (PROCEEDING SERIES OF PSYCHOLOGY, 2024)
Inclusive education is a form of government attention to students, especially children with special needs/Anak Berkebutuhan Khusus (ABK). Every child is given the same opportunity to get a proper education. However, there are still inclusive school institutions that have obstacles in their services. The purpose of this literature study is to provide an overview of the obstacles and efforts of elementary school institutions in improving services for children with special needs (ABK). This study uses an integrative literature review method. The literature is in the form of publications collected from the Garuda and web of science database in the period 2012-2022. The keywords used are "children with special needs" and "inclusive schools". From the keywords, 98 articles were obtained which were then screened, 13 articles were selected. The results of the review article revealed that the obstacles that are often encountered are limited special teachers and infrastructure, the difficulty of children with special needs receiving learning, and teachers' understanding. Then, the efforts are modifying curriculum, doing the workshop for teachers and students parents, improving teacher competence, using fun methods and media, repeating learning materials, and providing understanding to students who are not special needs to receive their special friends. The problem of inclusive problem that dominates are the lack of infrastructure and understanding of teachers in dealing with children with special needs, while efforts that can be made include increasing the understanding of school residents towards children with special needs and using various learning methods.
Keywords: Children With Special Needs; Inclusive Elementary School; Problem and Efforts